Extra-intestinal salmonellosis in a tertiary care centre in South India - Vithiya Ganesan; Shyamala Ravikoti; Raja Sundaramurthy; Monica Raghavan; Rajendran Tiruvanamalai (Iranian Journal of Microbiology, 2024)
Background and Objectives: Extra-intestinal salmonellosis is associated with higher case fatality and is underestimated in the developing countries like India. Here we present a case series of bacteriologically proven extra-intestinal salmonellosis managed at our institute over the past two years. Materials and Methods: Retrospective analysis of bacteriologically proven extra-intestinal salmonellosis over two years between January 2020 to December 2021 was carried out. Medical records were reviewed for site of infection, evidence of any underlying or predisposing illnesses and antimicrobial susceptibility report. Results: Eight patients were diagnosed with extra-intestinal salmonellosis. Male to female ratio was 3:1. Mean age was 44 years. Four were typhoidal and four were nontyphoidal Salmonellae. The extra-intestinal sites involved were purulent aspirates from scrotum, caecum, perianal region, intraperitoneal collection, synovium, and urine. Predisposing factors include chronic myeloid leukemia, HIV and gastric malignancy. All deep seated abscess required surgical intervention. All typhoidal Salmonella (n=4) were sensitive to cotrimoxazole, ampicillin, ceftriaxone. Among nontyphoidal Salmonella, one was resistant to cotrimoxazole; two were resistant to ampicillin, ceftriaxone and three resistant to ciprofloxacin. Conclusion: The diagnosis of extra-intestinal salmonellosis requires a high degree of clinical suspicion and should be included in the differential diagnosis in patients with deep-seated abscesses.